PERSPEKTIF KARYAWAN TELKOMGROUP TERHADAP INTERNALISASI CORE VALUES “AKHLAK” PADA BUDAYA ORGANISASI DI PT TELKOM INDONESIA (PERSERO) TBK. - Rini Aman Nasution; Muhardi, Muhardi; Frendika, Rusman (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
With the directive from the Ministry of State-Owned Enterprises of Indonesia regarding the need for core values in every state-owned enterprise (BUMN) under its supervision as an identity and adhesive of work culture that supports sustainable performance, where previously each BUMN had its own work culture. The purpose of this study is to investigate the perspective of TelkomGroup employees on the internalization and implementation of AKHLAK core values into the company’s culture using descriptive qualitative method in order to describe the perspective of TelkomGroup employees who are the targets and actors of the internalization and implementation of AKHLAK core values. Employee experience, length of employment, and work environment influence the perspective of TelkomGroup employees towards AKHLAK core values. The use of word "AKHLAK" in the core values is easier for employees to understand, making its internalization and implementation easier in both workplace behavior and community life.